Adolescents' Lifestyle Determinants in Relation to Their Nutritional Status during COVID-19 Pandemic Distance Learning in the North-Western Part of Romania-A Cross-Sectional Study - Bogdana Adriana Nasui; Rodica Ana Ungur; Gabriel Adrian Nasui; Codruta Alina Popescu; Ana Maria Hofer; Sebastian Dersidan; Monica Popa; Horatiu Silaghi; Cristina Alina Silaghi (MDPI AG, 2023)
Several studies have examined how the lockdown restrictions enforced to halt the spread of COVID-19 have affected adults' movement behaviors; however, there is limited information regarding the effects on youth. This study aimed to report on the lifestyle habits of adolescents during COVID-19 pandemic remote learning and explore associations between the participants' bodyweight and lifestyle behaviors. We used a cross-sectional study applied to 285 students studying in the gymnasium. The response rate was 74.21%. They completed an online questionnaire regarding lifestyle, eating habits, and nutritional status (assessed by the Body Mass Index-BMI). The study was conducted in January-February 2021. The percentage of overweight and obese was higher among boys (p = 0.001). The mean sleep duration was 8.12 (SD:1.284) hours per night, and was higher in boys than in girls. The respondents met the physical activity (PA) recommendation for their age, based mainly on unorganized PA. The screen time was 4-6 h or more for the majority of the respondents. Dietary habits included a high consumption of comfort food, like cereals, sweets, soft drinks, snacks, and fried food, but a lower consumption of vegetables and fast food. The regression analyses showed that the BMI was correlated with the BMI of the parents and the number of hours spent in front of the computers in free time. The study identified behavioral and environmental factors that can be modified with effective strategies to reduce overweight and obesity among school students and to promote a healthy lifestyle.